Individual, community, and societal drivers of adolescent peer violence in Asella, Ethiopia: A school-based cross-sectional study utilizing the socio-ecological model - Ayalneh Demissie; Tesfa G/meskel; Kasim Kimo; Muhammedawel Kaso; Yehwalishet Demeke; Tahir Aman; Yonas Mulugeta; Addis Wordofa (PLoS ONE, 2026)
Background Adolescent peer violence is a critical public health challenge in low- and middle-income countries. However, existing research in sub-Saharan Africa often focuses disproportionately on intimate partner violence or male-centered aggression, leaving a significant data gap regarding broader peer-to-peer dynamics in rapidly urbanizing Ethiopian settings. Furthermore, there is an urgent need for evidence that integrates psychosocial traits with environmental influences. This study addresses these gaps by utilizing the Socio-Ecological Model (SEM) —a framework that examines the interplay between individual, relationship, community, and societal factors—to investigate peer violence in Asella, Ethiopia. We specifically explore the role of General Self-Efficacy (GSE) , defined as an individual’s belief in their ability to perform across a variety of situations, as a potential driver of behavior. Our objective was to determine the magnitude of violence victimization and perpetration and to identify multi-level risk factors among school-going adolescents. Methods A school-based cross-sectional study was conducted among 542 adolescents (response rate = 99.5%) using a structured, self-administered questionnaire. Magnitude was assessed through standardized behavioral scales, and psychological resilience was measured using the General Self-Efficacy (GSE) scale. Multivariable binary logistic regression was utilized to identify independent predictors across the Socio-Ecological Model (SEM) levels. Results The prevalence of violence victimization was 41.6% (95% CI: 37.3–45.9%) and perpetration was 33.8% (95% CI: 29.7–38.1%). Based on bullying roles, 15.0% were “Bully-Victims,” who reported the lowest mean self-efficacy score (25.5 ± 3.6). Multivariable analysis revealed that low self-efficacy (≤28) was the strongest predictor for victimization ( AOR = 2.88 ; 95% CI: 1.95–4.26), while witnessing community violence was the primary driver for perpetration ( AOR = 2.52 ; 95% CI: 1.77–3.59). Male gender and belonging to the lowest wealth quartile significantly increased the odds for both outcomes. Conclusions Adolescent violence in Asella is a multi-dimensional public health issue driven by a cycle of low individual agency and environmental normalization of aggression. Strategies to mitigate this burden must move beyond the individual level. We recommend a comprehensive response that integrates school-based self-efficacy enhancement, community-level peace-building initiatives to reduce the impact of witnessed violence, and societal-level poverty alleviation. Such a multi-level approach is essential to disrupt the interplay between psychological vulnerability and environmental risk.